Representasi Konsep Kecantikan dalam Video Music SNSD Gee - Rima Nusantriani Banurea (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
Beauty is never ending concept. It always redefined,renewed, and reconstructed by actor who have a power likemedia to socializing and spreading it into the world. Thereforemedia can changing and determining what is the right conceptof beauty not only for now but also for future. Music Video isone of many forms of media which can spreading any ideas orconcepts like beauty amazingly through both a song and thestory. The successful of Music Video Gee makes Korean GirlBand, SNSD, famous and gets a lot attention from manycountries, like Indonesia. This Music Video is very fresh anddifferent from the other Music Videos of Korean Girl Band orBoy Band at that time. But, Music Video Gee is not neutral. Inthat video, there is hidden concept of beauty which trying torepresented by SNSD. This article will analyzing what is thecode of beauty like and how is the beauty represented in thatvideo.Keyword: Beauty, Music, Representation.